(untitled) (KEMANUSIAAN The Asian Journal of Humanities, 2013)
The Malay language has been a medium of Islamic discourse for several hundred years, functioning among others, as the language of translation and interpretation of the Qur'an and Hadith, as well as the language of Islamic epistemology, ontology and legal edicts. However, the colonisation of the Malay world by western powers has been responsible in secularising the Malay mind and language. As a result, secular knowledge is now given importance whilst Islamic revealed knowledge is considered as religious knowledge only. This article begins with a discussion on the Islamisation of the Malays and Malay language based on Syed Muhammad Naquib al-Attas' theory which underlines two elements (1) the infusion of the elements of rational and sound reasoning, and (2) the transformation of the Malay language into an Islamic language, enriched with Islamic vocabulary, which functions as a discourse on Islamic knowledge in various literary genres. The article argues that, from the Islamic perspective, western secular knowledge has caused confusion in defining facts, data, knowledge and others in the Malay language. Bahasa Melayu merupakan salah satu wadah pengucapan Islam setelah beratus-ratus tahun menjadi wacana penterjemahan dan pentafsiran al-Qur'an, al-Hadith, ulasan tentang epistemologi, ontologi, perundangan Islam dan sebagainya. Namun begitu, penaklukan dunia Melayu oleh kuasa Barat melalui proses sekularisasi ilmu, bahasa dan pemikiran telah memberi kesan terhadap pemikiran dan bahasa Melayu. Hal ini menyebabkan ilmu duniawi diberi keutamaan manakala ilmu agama Islam dianggap sebagai ilmu ukhrawi semata-mata. Perbincangan ini bermula dengan ulasan tentang proses Islamisasi umat Melayu dan bahasa Melayu berdasarkan teori Syed Muhammad Naquib al-Attas yang menyerapkan dua elemen, iaitu (1) unsur pemikiran rasional dan waras yang berbentuk akliah, logikal dan rasional, dan (2) mentransformasikan bahasa Melayu kepada bahasa Islam yang terserap dengan kosa kata Islam sebagai wadah pengungkapan dan penyebaran ilmu Islam dalam pelbagai genre persuratan. Artikel ini akan membahaskan bahawa dari sudut pandangan Islam, ilmu sekular Barat telah menimbulkan kekeliruan tentang konsep fakta, data, ilmu dan sebagainya dalam bahasa Melayu.